Service of process via social media in civil cases: an exploration of the potential use of social media platforms for bringing notice to defendants in Belgium - Cedric Vanleenhove (Revista Ítalo-Española de Derecho Procesal, 2020)
In common law systems, there has recently been a trend to permit plaintiffs to serve process on defendants through social media networks. This trend raises the following question: Is this form of service also beneficial in civil law countries, in particular, Belgium? To answer this question, this Article analyzes the conditions under which this type of service has been allowed by US courts, where most of the new development has occurred. This Article concludes that social media service may be a valuable additional means of notice when the defendant does not have a known address. In such circumstances, Belgian law currently prescribes service on the public prosecutor as the last resort method; however, service via social media platforms is far more effective at actually reaching the defendant. Consequently, the Belgian legislature could consider introducing social media service as a method supplementing service on the public prosecutor, provided the necessary safeguards are implemented.